2019
DOI: 10.3390/ijerph17010238
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Disability Pension, RTW-Intentions, and RTW-Behavior: Expectations and Experiences of Disability Pensioners over 17 Months

Abstract: Purpose: Individuals receiving a temporary disability pension (TDP) should get the opportunity to return to work (RTW). The current study aims to determine the factors contributing to RTW. Methods: 453 individuals on TDP were interviewed at three measurement points (T1, T2 = T1 + approximately 7 months, T3 = T1 + approximately 17 months). Socio-demographics, psychological predictors, and current work status (maintained TDP, permanent disability pension, old-age pension, employed, or receipt of other benefits) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
1
2
0
10
Order By: Relevance
“…Die Grundgesamtheit der potentiellen Teilnehmer bestand aus allen N = 4221 Versicherten der Deutschen Rentenversicherung (DRV) Oldenburg-Bremen, die im Untersuchungszeitraum eine befristete Erwerbsminderungsrente bezogen und nicht unter rechtlicher Betreuung standen. Das Studiendesign und ausgewählte Daten zur Baseline wurden bereits veröffentlicht [4,24]. Die Daten entstammen der längsschnittlichen Befragung mittels Computerassistierter, telefonischer Interviews (CATI).…”
Section: Materials Und Methodenunclassified
See 1 more Smart Citation
“…Die Grundgesamtheit der potentiellen Teilnehmer bestand aus allen N = 4221 Versicherten der Deutschen Rentenversicherung (DRV) Oldenburg-Bremen, die im Untersuchungszeitraum eine befristete Erwerbsminderungsrente bezogen und nicht unter rechtlicher Betreuung standen. Das Studiendesign und ausgewählte Daten zur Baseline wurden bereits veröffentlicht [4,24]. Die Daten entstammen der längsschnittlichen Befragung mittels Computerassistierter, telefonischer Interviews (CATI).…”
Section: Materials Und Methodenunclassified
“…Als weiterer theoretisch wichtiger Faktor für die Rückkehr in die Arbeit wurden im vorliegenden Modell keine Handlungsergebniserwartungen, also die positive und negative (subjektive) Bedeutung der früheren und möglicherweise zukünftigen Erwerbstätigkeit, berücksichtigt. Diese waren für die Absicht zur Rückkehr oder den tatsächlichen Rückkehrerfolg in einer anderen Analyse weni-ger bedeutungsvoll als Gesundheit und Alter [24]. Im Sinne eines möglichst ökonomischen Modells wurden diese Handlungsergebniserwartungen dementsprechend nicht berücksichtigt.…”
Section: Diskussionunclassified
“…Finally, empirical research on RTW continues its advancement, as the plethora of studies published during 2020 shows [87][88][89][90], while the systematic reviews and the methodological quality analysis of the existing literature [91] also contribute to expanding our comprehension of the RTW phenomenon as the main threat for the integration of people with health conditions in developed countries [5].…”
Section: Questionnairesmentioning
confidence: 99%
“…Return to work after a fixed-term disability pension has also been examined elsewhere. A German interview study found that a very small proportion of fixed-term disability pensioners returned to work, and it was clearly more common to receive a permanent pension [ 9 ]. Return to work seemed to be more likely among the younger and those with a shorter fixed-term pension, but due to the low number of those returning to work, the results are tentative.…”
Section: Introductionmentioning
confidence: 99%